2023
DOI: 10.1097/mao.0000000000003832
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options in Mal de Débarquement Syndrome: A Scoping Review

Abstract: ObjectiveThe purpose of this study was to review current treatment options available for mal de debarquement syndrome (MdDS).Data SourcesUsing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Review guidelines, we performed systematic search queries for MdDS-related texts. Documents must have been in the English language, and the time frame was all documents up until May 23, 2022.MethodsStudies were selected if they were published in a peer-reviewed journal and if on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…This is probably why their symptoms are ongoing. The actual review article (1) has shown a low success rate of vestibular rehabilitation, which agrees with the aforementioned description.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…This is probably why their symptoms are ongoing. The actual review article (1) has shown a low success rate of vestibular rehabilitation, which agrees with the aforementioned description.…”
supporting
confidence: 86%
“…The valuable review article by Kinkhabwala et al (1) concerning treatment options of mal de débarquement syndrome (MdDS) highlighted the need for collaboration because of the rarity of the disease process. Based on our clinical experience of more than thousand patients suffering from chronic multicanalicular benign paroxysmal positional vertigo (mc-BPPV), we consider mc-BPPV as a major cause of MdDS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another drawback of these types of medications is their potential for addiction [ 8 ] and the development of tolerance [ 17 ], limiting prolonged usage. Other non-specific treatments, such as standard vestibular rehabilitation, chiropractic treatments, vestibular suppressants, and counselling, have been trialed with no substantial benefits [ 12 , 16 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It affects their employability, social life, and will to live ( 2 , 4 ). While there exists a range of treatment options, including pharmacological interventions, neuromodulation, and vestibulo-ocular reflex (VOR) rehabilitation, their accessibility is limited, or they primarily address secondary symptoms rather than resolving the underlying issue ( 5 ). Therefore, adequate treatment options capable of diminishing MdDS symptoms are of great importance.…”
Section: Introductionmentioning
confidence: 99%